Dissolved organic matter and its optical characteristics in the Laptev and East Siberian seas: spatial distribution and interannual variability (2003–2011); Ocean Science; Vol. 14, iss. 1 - Pugach S. P. Svetlana Petrovna; Pipko I. I. Irina Ivanovna; Shakhova N. E. Nataljya Evgenjevna; Shirshin E. A. Evgeny; Perminova I. V.; Gustafsson O. Orjan; Bondur V. G. Valery; Ruban A. S. Aleksey Sergeevich; Semiletov I. P. Igor Petrovich (2018, 2018)
Title screen